Perilaku Pemilih dalam Menentukan Keputusan Politik di Indonesia pada Awal Era Reformasi - syaripudin, syaripudin; Umaternate, Rifandi; Farhani, Muhammad Jundi; Izzatusholekha, Izzatusholekha (Peneliti.net, 2024)
This study examines the political phenomena in Indonesia during the reform era, focusing on voter behavior in general elections. The reform era, which began with the fall of the New Order government in 1998, marked a transformation in the Indonesian political landscape, characterized by an increase in political freedom and the freedom to form political parties. Adopting the Public Choice Theory, this research analyzes data from the 1999, 2004, 2009, and 2014 elections to understand voter motivations. The findings indicate that voters tend to use a sociological approach in determining their political choices, with factors such as regional similarity, race, and loyalty to political parties as key influencers. These conclusions aim to provide insights into the post-reform era political dynamics and voter behavior in Indonesia.